THE IMPACT OF OPTIMAL PROFIT TAXATION ON INVESTMENT ATTRACTION - Zarif Ahrorov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the current economic conditions, most countries of the world are moving along an innovative path of development and use various financial and non-financial instruments for this. One of these financial instruments is the income tax, which in turn is the object of combining the interests of the state, enterprises and the population. Therefore, this study is aimed precisely at the analysis of the formation of a unified income tax system that contributes to the inflow of investments into the innovative development of both the state and an individual enterprise. To date, a large number of financial incentives for innovation are used, such as tax incentives, loans, state subsidies, however, practice shows that not all of them give the desired effect. The formation of a unified system of taxation of profits will create a synergistic effect from the financial mechanism for stimulating investment in innovative development.